Transforming Vietnam’s Rice Sector: A Pathway to Low-Emission Agriculture - Sharick, Amber; Tan, Cherie (2025)
This paper presents a selected set of recommendations developed through recent dialogues and workshops in 2024, involving a diverse group of stakeholders within the rice ecosystem. These recommendations are designed to support Vietnam’s ambitious one-million-hectare low-emission rice initiative by addressing key challenges such as financing, technological integration, capacity building, and equitable benefit-sharing. By reflecting the insights of experts across the rice value chain, the paper offers a roadmap for driving the transformation needed to meet Vietnam’s sustainability and climate goals.